Antibacterial carbon dots - Shuaishuai Wang; Dapeng Wang; Guoliang Wang; Minglei Zhang; Yirong Sun; Jianxun Ding (Materials Today Bio)
Bacterial infections significantly threaten human health, leading to severe diseases and complications across multiple systems and organs. Antibiotics remain the primary treatment strategy for these infections. However, the growing resistance of bacteria to conventional antibiotics underscores the urgent need for safe and effective alternative treatments. In response, several approaches have been developed, including carbon dots (CDs), antimicrobial peptides, and antimicrobial polymers, all of which have proven effective in combating bacterial resistance. Among these, CDs stand out due to their unique advantages, including low preparation cost, stable physicochemical properties, high biocompatibility, tunable surface chemistry, strong photoluminescence, and efficient generation of reactive oxygen species. These features make CDs highly promising in antibacterial applications. This review explores the development of antibacterial CDs, focusing on their mechanisms of action—physical destroy, biochemical damage, and synergistic effects—while highlighting their potential for clinical use as antibacterial agents.